Peningkatan Hasil Belajar Pendidikan Agama Islam Dengan Menggunakan Media Audiovisual di Kelas V UPTD SDN 05 Suayan - Elvi Yanti Martini; Zulfani Sesmiarni; Rodi Rodi; Desri Wahyuni; Meyriza Hamda; Yona Widia Eka Putri (Jurnal Pendidikan Tuntas, 2024)
ABSTRACT This research is motivated by the low learning outcomes of Islamic Religious Education students in Class V UPTD SDN 05 Suayan. By using audiovisual media in learning will greatly help students' understanding. The purpose of this study is to: determine the increase in Islamic Religious Education (PAI) learning outcomes of students through audiovisual media in class V UPTD SDN 05 Suayan. Data collection techniques used are tests and observations. The results of the study indicate that audiovisual media in PAI subjects can increase students' learning motivation, especially class V students of UPTD SDN 05 Suayan. Quantitative evidence can be seen from the increase in the motivation variable test from the first meeting and the second meeting. From the test results, there was also an increase from the pre-action results of 45%, in cycle I (first) it increased to 60%, in cycle II (second) it also increased to 90%. While qualitative evidence can be explained from the number of students who expressed their pleasure in the use of this audiovisual media, the growth of motivation, student concentration on PAI subjects.